PREGNANCY AND CHILDBIRTH IN A PATIENT WITH SPINAL MUSCULAR ATROPFY (CLINICAL CASE) - Ирина Анатольевна Ушакова; Нонна Марковна Шибельгут; Игорь Анатольевич Гнусарев; Екатерина Владимировна Литовченко; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина (The Publishing House Medicine and Enlightenment, 2020)
Spinal muscle atrophy (SMA) is a group of diseases inherited by an autosomal recessive type and characterized by degeneration of cells of the anterior horns of the spinal cord. The disease leads to progressive atrophy and weakening of skeletal muscles. There are spinal muscular atrophies with a frequency of 1 : 25000 people, the frequency of heterozygous carriage is 1 in 40-60 people.